The Implementation of Inclusive Education in Arabic Learning for Blind Students/ تنفيذ التربية الشاملة في تعليم اللغة العربية للتلاميذ المعاقين ضعف البصر - Maftuhaturohmah, Maftuhaturohmah (ATHLA : Journal of Arabic Teaching, Linguistic and Literature, 2020)
Every citizen has the right to education. Likewise, the right to teach Arabic, which is one of the subjects taught in schools, is not only taught to ordinary students, but also to students with physical limitations. The purpose of this study was to describe the implementation of Arabic language learning in an inclusive class. Learning Arabic in an inclusive classroom is a general class between ordinary students and students with special needs (visually impaired). In learning Arabic in an inclusive class, teachers experience difficulties because they do not have special teaching skills in an inclusive class. The readiness of teachers in preparing teaching materials that can be accessed by blind students is the key to the success of learning Arabic for blind students.